The Effectiveness Of Al-Quran Murottal Therapy On Hemodynamic Status During Intraoperative - Tati Hardiyani; Atikah Dhiah Anggraeni; Ulfa Azizah (Jambura Nursing Journal, 2023)
Intraoperatif Surgery is an invasive treatment by opening or showing body parts. In general, this is done by making an incision in the part of the body that will be treated and repaired, and this ends with closing and suturing the wound. Patients undergoing surgery using general anesthesia often experience changes in hemodynamic status. It is essential to pay attention to hemodynamic status and provide intervention so that it does not interfere with the operation and threaten the patient's life. One of the interventions to stabilize hemodynamics in general anesthesia patients is listening to murottal Al-Qur'an. This study aimed to determine the effect of giving murottal Al-Qur'an therapy on hemodynamic status during intraoperative at Wijayakusuma Hospital, Purwokerto. Quasi-experimental research design with pre-test and post-test design without control group design was employed. The sampling technique used non-random sampling with total sampling. The data were analyzed through non-parametric. This study showed that the pre-test and post-test values of hemodynamic status on systolic blood pressure decreased in the intervention group (p=0.01) but not in the control group (p=0.501). The intervention group showed significant improvement over the control group in systolic blood pressure (p=0.041) but not in diastolic blood pressure (p=0.341), HR (p=0.698), RR (p=0.583), and SpO2 (p= 0.429). Statistically, hemodynamic status experienced a significant difference in systolic blood pressure. Conclusion: Giving murottal Al-Qur'an therapy affects hemodynamic status during intraoperative at Wijayakusuma Purwokerto Hospital on systolic blood pressure.